Parents' perspectives on the value of assistance dogs for children with autism spectrum disorder: a cross-sectional study. Issue 6 (13th June 2014) - Burgoyne, Louise; Dowling, Lisa; Fitzgerald, Anthony; Connolly, Micaela; P Browne, John; Perry, Ivan J
Abstract : Objective: While there is an emerging literature on the usefulness of assistance dogs for children with autism spectrum disorder (ASD), there is a dearth of quantitative data on the value of assistance dog interventions for the family unit and family functioning. Using previously validated scales and scales developed specifically for this study, we measured parents'/guardians' perceptions of how having an assistance dog affects: (1) child safety from environmental dangers, (2) public reception of ASD and (3) levels of caregiver strain and sense of competence. We also obtained open-ended response data from parents/guardians on benefits and constraints of having an assistance dog. Setting: This study was based in the primary care setting, within the context of a specific accredited assistance dog centre in Ireland. Participants: A total of 134 parents/guardians with an assistance dog, and 87 parents of children on the waiting list were surveyed. Primary and secondary outcome measures: The primary outcome measures were scores on environmental hazards and public reception scales. The secondary outcome measures were scores on caregiver strain and competence scales. Results: Parents/guardians of children who have ASD and an assistance dog rate their child as significantly safer from environmental dangers (p<0.001), perceive that the public act more respectfully and responsibly towards their child (p<0.001) and feel more competent about managing their child (p=0.023) compared with parents on the waiting list. There was a concentration of positive feeling towards assistance dog interventions with particular focus on safety and comfort for children, and a sense of freedom from family restrictions associated with ASD. The amount of dedication and commitment required to care for a dog were viewed as the primary constraints. Conclusions: Our findings indicate that parents perceive that assistance dog interventions can be a valuable intervention for families with children who have ASD.